2020
DOI: 10.1021/acs.jpca.9b10538
|View full text |Cite|
|
Sign up to set email alerts
|

Exchange-Correlation Energy Densities and Response Potentials: Connection between Two Definitions and Analytical Model for the Strong-Coupling Limit of a Stretched Bond

Abstract: We analyze in depth two widely used definitions (from the theory of conditional probability amplitudes and from the adiabatic connection formalism) of the exchange-correlation energy density and of the response potential of Kohn−Sham density functional theory. We introduce a local form of the couplingconstant-dependent Hohenberg−Kohn functional, showing that the difference between the two definitions is due to a corresponding local first-order term in the coupling constant, which disappears globally (when inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
1
12
0
Order By: Relevance
“…It is negative everywhere in a position space and hence it yields a stabilizing contribution to the energy density. The static response potential, vxresp()r > 0, measures sensitivity of the exchange correlation to the electron density variations and only makes a destabilizing second‐order contribution to the energy density; therefore, it is neglected in this study 52,69–71 …”
Section: Methodsmentioning
confidence: 99%
“…It is negative everywhere in a position space and hence it yields a stabilizing contribution to the energy density. The static response potential, vxresp()r > 0, measures sensitivity of the exchange correlation to the electron density variations and only makes a destabilizing second‐order contribution to the energy density; therefore, it is neglected in this study 52,69–71 …”
Section: Methodsmentioning
confidence: 99%
“…Here, v x, hole (r) < 0 is the potential resulting from the exchange-hole charge density, while v x, resp (r) > 0 describes the response of exchange screening to small density variations, when preserving the number of electrons. The last term is $10 times less than v x, hole in absolute value and it is not expressed via electron density (Nagy & March, 1992;Gritsenko et al, 1996Gritsenko et al, , 2016Fuentealba, 1997;Nagy, 2010;Kohut et al, 2016;Giarrusso & Gori-Giorgi, 2020;Kreisler, 2020). We also found that the local density approximation (LDA), gradient expansion approximations, generalized gradient approximation (Parr & Yang, 1989) and empirical approximations to v x, resp give unrealistic exchange potentials and do not provide the expected formation of electron shells.…”
Section: Methodsmentioning
confidence: 81%
“…Unfortunately, a reliable local-density approximation for potential v P (r) is unknown (Levy & Go ¨rling, 1994;Finzel, 2016;Nagy, 2018;Giarrusso & Gori-Giorgi, 2020). Moreover, the gradient expansion of T P violates the exact condition v P (r) !…”
Section: Methodsmentioning
confidence: 99%
“…[30]) and that the different kinetic energy densities of the interacting and the KS system fully account for the differences between v G and v PG . Hence, v G has been called the "kinetic potential" in the literature [31,43].…”
Section: The Geometric Potentialmentioning
confidence: 99%
“…The separation of a wavefunction into a marginal and a conditional part was first considered for the electron-nuclear problem [29] and has subsequently been transferred to the many-electron problem [27], which lead to first studies of the properties of and the connections between v, v KS , and v P , for atoms [30][31][32][33] and diatomics [30,[34][35][36], and to further studies of the conditional wavefunction in the DFT literature [37][38][39][40][41][42][43][44]. Recently, the formalism of the wavefunction separation has been further developed for the electron-nuclear problem and been termed the exact factorization [45][46][47].…”
Section: Introductionmentioning
confidence: 99%